Practices of managers and their impact on the contributions of personnel - سموعي رفاء فرج (Journal of Economics and Administrative Sciences, 2012)
This research was based on two pillars. The first is a comparison between of research done and the result of a particular variable of research indebendently in the united state, and second, knowledge and determine the effect of managers practices on the contributions of personnel. The manager and staff are considered to be the most important elements in the organization and all of them have a duty towards the others which governed by the relationship rules of procedure of the ministry researched, on the one hand and the interests of the organization and hence employees , whether executives or employees within management formations that the availability of an acceptable level of good practices or contributions to pave the way towards success and progress and if any delay action or harm happened in any of its parts this would affect the organizations interest. The research seeks to dignose the levels of managers practices impact on employees contributions in the field of (commitment,woking actively and creativity) within a contemporary vision of the modern administration in the ministry research (Industry and Minerals), the research depended on the descriptive analytical approach in the treatment of variables . It expressed the research problem as a set of questions that reflectd the problem research scheme ,which put forward two major hypotheses and six subsidiary hypotheses. this study applied on a sample of (98) executives in the ministry and adopted a questionnaire as an essential tool for collection of data and information (in addition to conducting interviews) which were processed using a number of statistical methods(mean,standard deviation, coefficient of variation, simple regession analysis). The research found a number of conclusions and specially the presence of impact of the total managers practices(accountability,promotion,development)in the total contribution of staff. It was also obvious that there was no difference with what were there in Americ a while the contributious of employees were better than in the area of (working actively, creativity ). The most important recommendatious that the research has stressed is the need for the manager who adopt accountability procedure practice with a more serious and a kind of objectivity in the application and staying away from its performance as a routine procdure and there should be a continuous follow up with details to see the results and make them effective by highlighting the benefits and positives of accountability for the work , for the employees of the organization and for the clientele of the beneficiaries.